Distribusi serotipe Actinobacillus Actinomycetemcomitans pada periodontal=Distribution of Actinobacillus Actinomycetemcomitans Serotype in the Periodontal - Witjaksono, Widowati (Airlangga University Press, 2000)

(untitled)
The aim of this study is to determine the distribution of Actinobacilus actinomycetemcomitans serotype on healthy and periodontal disease patients by indirect immunofluorescence and/or immunodiffusion method and to know specific serotype with polyclonal antisera against Actinobacillus actinomycetemcomitans serotype a, b and c. Data was obtained from 177 Actinobacillus actinomycetemcomitans isolated from 136 individuals with four catagory studies. The result shows that the three serotypes of Actinobacillus actinomycetemcomitans are found in all catagory studies and there is a significant difference between a healthy and a periodontal disease in the distribution of Actinobacillus actinomycetemcomitans serotype a, b and c (p = 0.00l) Isolation cultured on an anaerobic and aceton fixation and isolation cultured on a 10% CO2, and heat fixation reveal positive fluorescence against one antiserum only. However there is isolation which reacts positively with two antisera, where the most occuring fact is an antisera b/c and lhe least is an antisera a/c. Besides that, it reveals not in accordance immuno fluorescence reaction related with culturing and fixation method, also there is an isolation that could not be serotyping by immunodiffusion assay